The Impact of Implementing a Collaborative Learning Model on the Learning Independence of Prospective Science Teacher Students in Developing Educational Media - Mashuri, Mohan Taufiq (JURNAL PENDIDIKAN & PENGAJARAN (JUPE2), 2025)
This study aims to investigate the impact of implementing a collaborative learning model on the learning independence of prospective science teachers in developing learning materials. This study employs a quasi-experimental design with a mixed-methods approach, utilizing a posttest-only non-equivalent control group design. The research sample consisted of 34 prospective science teachers selected from one of the state universities in Indonesia and divided into two groups: the experimental class and the control class. The experimental class received treatment through the implementation of a collaborative learning model, while the control class used a regular learning model. Data were collected using a learning independence score instrument, student reflection journals, and observation sheets to assess the implementation of the learning model. Analysis of the questionnaire data began with conducting validity and reliability tests to evaluate the Learning Independence Questionnaire, followed by normality and homogeneity tests on the Learning Independence data between the experimental and control classes. Hypothesis testing was conducted using an independent t-test. The results of the validity and reliability tests indicate that the Learning Independence Questionnaire is suitable for use. The results of the hypothesis test suggest that implementing a collaborative learning model can enhance the learning independence of prospective science teachers in developing learning materials. In addition, based on the reflection journal and observation sheet, it is also evident that the experimental class had better development of learning media results compared to the control class.